Desain Analisis Semantik Alquran Model Ensiklopedik: Kritik atas Model Semantik Toshihiko Izutsu - Dadang Darmawan; Irma Riyani; Yusep Mahmud Husaini (AL QUDS : Jurnal Studi Alquran dan Hadis, 2020)
The Qur’anic Semantic Analysis of Encyclopedic Model: Critics to Semantic Model of Toshihiko IzutsuThis research attempts to build a new model of semantic analysis to the Qur’anic text, which is called encyclopedic semantics. This research contributes to the improvement of Qur’anic semantic analysis of Izutsu and as an alternative model. This article employs a qualitative method and research and development (R & D) with analytical descriptive to the data gathered. Analysis of the data consist of several steps, namely analyzing Izutsu’s model of Qur’anic semantics, identifying and verifying several limitations on Izutsu’s model, building a new design of Qur’anic semantics to perfection, and lastly, demonstrating the new model in the semantics applied to the Qur’anic text. This research shows that based on the laxity found in Izutsu’s model, this research creates a new model of semantics analysis to the Qur’an called encyclopedic semantics as an alternative model to the existing model from Izutsu. The semantics model of encyclopedic perfects the Izutsu model with significant differences. The semantics model of encyclopedic aims at rendering the meanings of the Qur’an from global to particular.  In contrast, the Izutsu model is to achieve meanings from particular to global. Besides, encyclopedic model of semantics is part of mawdlu’iy (thematic) method of interpreting the Qur’an. This model gains its legitimation from Islamic tradition. The sample of this model is shown in the application of the Qur’anic word maṭar.